The Ethics of Journalism: Individual, Institutional and Cultural Influences - Wyatt, W (2014)
The landscape in which journalists now work is substantially different to that of the twentieth century. The rise of digital and social media necessitates a new way of considering the ethical questions facing practicing journalists. This volume considers the various individual, cultural and institutional influences that have an impact on journalistic ethics today. It also examines the links between ethics and professionalism, the organisational promotion of ethical values and the tensions between ethics, freedom of information and speech, and the need to disseminate information. By comparing the theoretical underpinnings of journalistic ethics with a variety of international case studies, this volume provides a comparative global analysis of the ethical challenges faced by the media in the twenty-first century. It will be essential reading for students of journalism and practising journalists.